Effect of Statins on Liver Function Tests (LFTs) in Patients with Diabetes Presenting in CMH Rawalakot - Zia, Tayyiba (Indus Journal of Bioscience Research, 2025)
Objectives: To find the effect of statin therapy on liver function tests in diabetic patients presenting at CMH Rawalakot. Study design: Qausi-experimental study. Place and duration of study: Department of Medicine, CMH, Rawalakot, from October 2024 to March 2025. Methodology: A total of 100 patients, aging between 40 to 70 years, diagnosed with type 2 diabetes since ≥1 year, and was not previously on statin therapy, were included in this study using consecutive sampling. All the demographics and related medical history was recorded. Baseline liver function tests (ALT, AST, ALP, GGT, and total bilirubin) and the blood glucose levels were recorded. Patients were recommended Rosuvastatin 20 mg/day for 3 months. The primary objectives of the study was to find the impact of statin therapy on liver function tests in diabetic patients presenting at our hospital. Values of Pre- and post-treatment LFT were compared using the paired t-test, with a p-value <0.05 taken as statistically significant. Results: The mean age in this study was 50.38±6.89 years (ranging from 36 to 64 years). The male gender was 58% of total study population while female gender was 42%. Comparison between baseline and post-treatment liver function test values after 3 months of statin therapy with Rosuvastatin 20 mg/day showed no statistically significant change in all the parameters of LFTS including ALT (p=0.14), AST (p=0.79), ALP (p=0.11), GGT (p=0.88) and total bilirubin levels (p= 0.17). The analysis of sub-group of patients with HbA1C levels ˃7% also showed no statistically significant change in LFTs. Conclusion: Statins are hepatically safe in diabetic patients, with no significant changes in liver function tests, supporting its clinical use for managing dyslipidemia in these patients.